Micro-CT reconstruction reveals new information about the phylogenetic position and locomotion of the Early Cretaceous bird Iberomesornis romerali - Terol, Javier C.; Pérez-Ramos, Alejandro; O’Connor, Jingmai K.; Sanz, José Luis; Serrano-Lozano, Francisco (Elsevier, 2025)
The enantiornithine Iberomesornis romerali from the Lower Cretaceous site of Las Hoyas (Spain) was originally described more than 35 years ago. As one of the first known articulated partial skeletons of this clade, I. romerali has been critical to our understanding of early avian systematics. Due to its preservation as a largely two-dimensional slab specimen, previous anatomical descriptions were unable to fully capture its anatomy. Here, we present new anatomical data based on micro-computed tomography of the holotype. We reconstruct five previously poorly known osteological elements, i.e., cervical vertebrae, pygostyle, coracoid, furcula, and humerus. Re-evaluation of these elements resulted in revised scorings for 15 morphological characters commonly used for cladistic analysis of Aves. The results of the modified character matrix support Iberomesornis in a derived position within Enantiornithes, close to the Longipterygidae. In addition, new findings in the coracoid and humerus reveal well-developed muscles for the elevation (i.e., supracoracoideus) and flexion–extension (extensor carpi radiale) of the wing. The new evidences, together with the typical enantiornithine furcula and the small size of the holotype, suggest that I. romerali was capable of flapping flight.
Keywords: Paleontología - Mesozoico; Aves - Evolución; Tomografía; Enantiornithes; Mesozoic birds; Avian evolution; Computed tomography scanning; Bone reconstruction; Flight mechanics; Las Hoyas